2021
DOI: 10.1590/0103-6440202104127
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of Botulinum toxin A for improving esthetics in facial complex: A systematic review

Abstract: Aim: To evaluate efficacy and safety of Botulinum toxinA for improving esthetics in the facial complex and correlating them to the dosage and side effects through a systematic review. Methods: A literature search was performed using PubMed, Medline, Web of Sciences, and Scopus databases. Quality of studies was appraised through the GRADE system. This review follows the ‘Preferred reporting items for systematic review and meta-analysis protocols’ (PRISMA-P) 2015 statement. Efficacy was analyzed through improvem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The digital dermoscopy evaluation performed in our study revealed an evident reduction in the caliber of the telangiectasias, an effect which persistent until the end of the study. This is a new finding which has not been reported in previous studies [ 6 , 11 ].…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The digital dermoscopy evaluation performed in our study revealed an evident reduction in the caliber of the telangiectasias, an effect which persistent until the end of the study. This is a new finding which has not been reported in previous studies [ 6 , 11 ].…”
Section: Discussionsupporting
confidence: 64%
“…Several studies suggested that injections of microdoses of BTX-A may be an effective procedure for the management of excess facial sebum, facial pores, papules and pustules, facial erythema, and rosacea [ 6 , 10 , 11 ]. The generalizability of the results of those studies, however, is limited due to the heterogeneity in the population being studied, the distinct treatment protocols being evaluated, the assessment methods utilized to measure the outcomes and the different brands of the BTX-A studied [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…The patients mean age was 44.8 which consist with other studies. [7][8][9] American Society for Aesthetic Plastic Surgery statistics reported that 77% of BTX-A procedures were administered to patients of age 35-64, in 2011. 10 BTX-A injections usually preferred between early thirties and fifties before the facial wrinkles become static.…”
Section: Discussionmentioning
confidence: 99%
“…Among the studies, the most common side effect reported was headache. 9,20,21 In a multidepartment study, 5310 treatment of BTX-A for multiple indications, 184 (3.73%) adverse events reported. 114 (2.26%) of them were muscle-related and the most common was ptosis.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that it is necessary to carry out a formal meta-analysis to increase the validity of the evidence synthesis for the effectiveness of BoNT in OBPI [ 17 ]. Additionally, patient demographics such as age have been found to be correlated to BoNT effectiveness when applied for purposes other than OBPI [ 18 , 19 ], and whether similar relationships can be found in OBPI deserves exploration.…”
Section: Introductionmentioning
confidence: 99%